Hybrid NarrowBand-internet of things protocol for real time data optimization - Denny Kurniawan; Muhammad Ashar; Harits Ar Rosyid (Institute of Advanced Engineering and Science, 2023)
The level of dependence on data communication in the modern era is increasing exponentially. The internet of things (IoT) plays a very important role in the advancement of the industrial revolution 4.0 that utilizes data communication systems. IoT deployments require data communication protocols, such as hypertext transfer protocol (HTTP), and message queuing telemetry transport (MQTT) as well as network communication protocols (wireless) to meet the network needs of devices with limited resources. Optimization of data communication in IoT is needed to maintain the quality of sending and receiving data in real time. This research proposes a hybrid NarrowBand-IoT (NB-IoT) protocol designed using NarrowBand communication network technology with optimization of data communication using MQTT and HTTP protocols. In this research, the hybrid NB-IoT protocol has the best packet loss value of 0.010% against the HTTP NB-IoT protocol which has a value of 0.017%, and the MQTT NB-IoT protocol of 0.024%. The hybrid NB-IoT protocol has a latency value of 8.7 seconds compared to the HTTP NB-IoT protocol which has a latency of 10.9 seconds. Meanwhile, the throughput value of the hybrid NB-IoT protocol is 158906.1 byte/s and is better than the MQTT NB-IoT protocol which is only 158898.6 bytes/s.